Pengaruh Umur Dan Posisi Vertikal Batang Terhadap Beberapa sifat Mekanika Bambu Apus (Gigantoclia apus Kurz)*) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT The objective of this research is to observe the effect of two factors, namely age and axial position on the mechanical properties of Giganthochloa apus Kurz (bamboo). Research was conducted on 3 stems of G. apus at five groups of age, i.e 2, 3, 4, 5 and 6 years old. Each stems was cut into 3 parts, butt, middle and upper. Static bending and compression strength parallel to grain of the bamboo was determined using modified ASTM D 143-52 and Janssen method. Results show that age factor significantly effects compression parallel to grain, but not static bending strength. The highest value of the compression parallel to grain exerted by 5 year-old bamboo Modulus of rupture and modulus of elasticity at that age were 33,55 MPa and 0,67 GPa respectively. Position along the stem also shows a significant effect on the mechanical properties. For compression parallel 10 grain, the higher the position on the stem the higher the strength.